Strategies for Achieving Audit Quality: The Big 4 Model - Mark Francis Ng (Recoletos Multidisciplinary Research Journal)
Audit quality is essential for maintaining public confidence in the audit profession. This paper explores the strategies utilized by Big 4 auditing firms in attaining the regulatory mandate of audit quality during the last decade and translates these into a conceptual model as a benchmark for other auditing firms. Using an in-depth document analysis of annual reports subjected to a blended (abductive) coding approach utilizing descriptive and longitudinal methods, this research found that value creation for significant stakeholders served as the foundation for implementing initiatives related to audit quality. Common priorities and practices include client engagement, strategic investments, technology innovation, market leadership, workforce empowerment, streamlined operations, regulatory compliance, and social responsibility. These findings reshape the way we view the identity of auditing firms as comprehensive organizational entities other than being mere external assurance providers and emphasize the significance of audit quality, particularly when viewed from a firm-level or managerial perspective.